1982
DOI: 10.1021/j100221a030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization by Moessbauer spectroscopy of iron carbides formed by Fischer-Tropsch synthesis

Abstract: Recent Móssbauer spectroscopy results on iron carbides formed by Fischer-Tropsch synthesis are discussed.For carbides with carbon in octahedral sites (named here 0 carbides), we show that V-Fe2,2C" and "e-Fe2C" really correspond to Fe2C and ~Fe2.2C, respectively. A departure from hexagonal symmetry of the C atom arrangement is deduced for ~Fe2C while the limiting compositions are Fe2 4±tl lC and Fe2C. Simple relations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(60 citation statements)
references
References 0 publications
7
53
0
Order By: Relevance
“…For instance, metallic iron is observed in hydrogen, cementite, and Hägg carbide are the main phases in CO and in syngas, respectively. And iron carbide is also observed to have ε-χ-θ transition behavior during the FTS reaction at different conditions [154] confirming the structure evolution of iron oxide catalyst from hematite to magnetite and finally to iron carbide in the FTS [155]. It is well recognized that the activation conditions before the FTS reaction can influence the final iron structure in the steady reaction conditions [156].…”
Section: Characterization Of Fts Nanostructured Catalystssupporting
confidence: 61%
“…For instance, metallic iron is observed in hydrogen, cementite, and Hägg carbide are the main phases in CO and in syngas, respectively. And iron carbide is also observed to have ε-χ-θ transition behavior during the FTS reaction at different conditions [154] confirming the structure evolution of iron oxide catalyst from hematite to magnetite and finally to iron carbide in the FTS [155]. It is well recognized that the activation conditions before the FTS reaction can influence the final iron structure in the steady reaction conditions [156].…”
Section: Characterization Of Fts Nanostructured Catalystssupporting
confidence: 61%
“…A great deal of information on the structure of iron carbides was collected by Nagakura and Oketani (22) and Le CaEr et al (34). A few relevant data are summarized here.…”
Section: Iron Catalystsmentioning
confidence: 98%
“…For nickel it has been suggested that graphite nucleates in the bulk of the carbide phase leading to fractionation of the metal crystallites (42). Also in the case of iron, Le Caer et al (34) supposed that the relative increase of the contribution of superparamagnetic iron carbide to the Mossbauer spectrum could be explained by fragmentation of particles. For supported catalysts the metal particles seem to fragment most probably where mechanical stresses are easiest to dissipate, that is, at the metal-gas interface or near the metal-support interface.…”
Section: Initiation and Mechanismmentioning
confidence: 99%
“…[3] Iron-based catalysts are widely used in Fischer-Tropsch synthesis (FTS) [4,5] with iron carbides giving high levels of activity and selectivity in producing the desired longer hydrocarbon chains. [6] Characteristics of iron carbides as compounds may vary greatly, as summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%